Effects of Terpinen-4-ol on meibomian gland epithelial cells in vitro - Chen, Di (Cornea, 2020)
PURPOSE: Infestation with Demodex mites has been linked to the development of chalazion, meibomian gland dysfunction and blepharitis. An effective treatment is the eyelid application of terpinen-4-ol (T4O), a tea tree oil component. However, T4O is also known to be toxic to non-ocular epithelial cells. We hypothesize that T4O toxicity also extends to human meibomian gland epithelial cells (HMGECs). METHODS: Immortalized (I) HMGECs were cultured with varying concentrations (1.0 to 0.001%) of T4O under proliferating or differentiating conditions up to 5 days. Experimental procedures included analyses of cell appearance, survival, P-Akt signaling, lysosome accumulation, and neutral lipid content. RESULTS: Our findings show that T4O causes a dose- and time-dependent decrease in cell survival of IHMGECs. After 15 minutes of exposure to 1% T4O, IHMGECs exhibited rounding, atrophy and poor adherence. Within 90 minutes of such treatment, almost all cells had died. Reducing the T4O concentration to 0.1% also led to a marked decrease in P-Akt signaling and cell survival of IHMGECs. Decreasing the T4O amount to 0.01% caused a slight, but significant, reduction in IHMGEC number after 5 days of culture, and did not influence the ability of these cells to differentiate. CONCLUSIONS: T4O, even at levels 10- to 100-fold lower than demodicidal concentrations, is toxic to HMGECs in vitro.